Orders, production, and investment; a cyclical and structural analysis. - Zarnowitz, Victor; Columbia University Press (New York, National Bureau of Economic Research, 1973)
This book was developed from a study mainly concerned with the characteristics of manufactures' new order as a type of leading indicator of business changes. It also deals with the cyclical aspects of selected variables and their relationships.
includes index
Includes bibliographical references.
occ 16/01/2019
Loans
Keywords: Business cycles; Industrial procurement; Capital investments; Inventories